Assessment of some technical parameters of elite male tennis players according to world rankings - Arabaci, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Purpose The objective of present study was to compare some technical parameters of male tennis players in the top 10 (G1) and 11-200 (G2) rankings in the last week of 2023 Association of Tennis Professionals (ATP).